Histological features of kidney observed through conventional microscope and paper microscope - Singh, Poonam; Phuyal, Naveen; Paudel, Sushanta (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Introduction: Paper microscope (Foldscope), one of the latest inventions in the field of science is an ultra-low cost, portable, versatile, and water proof microscope which does not require electricity. The aim of this research was to compare histological features of kidney observed in the normal microscope and foldscope. This research is focused on the comparison of the histological features of kidney observed in the conventional microscope and foldscope under 100X.Method: This comparative study was conducted in Department of Anatomy, Nepalese Army Institute of Health Sciences, Nepal. All histological slides of kidneys present at Department of Anatomy during June 2019-September 2019 were included in this study.Result: A total of 25 samples were viewed under the conventional laboratory microscope (C x L and Paper Microscope (Foldscope). Foldscope observers were able to distinguish the histological features of the cortex and the medulla of the kidney along with the difference in the luminal size and the staining of the cells in the cortex and the medulla of the kidney. In comparison to conventional microscope, 5 (20%) of samples, observers were able to distinguish the features of the cells lining the tubules of the cortex and in 6 (24%) of samples, observers were able to distinguish the features of the cell lining collecting duct and straight tubules of loop of Henle of medulla using Foldoscope.Conclusion: Paper microscope can be a useful alternative of conventional microscope in low resource settings for the identification of the histological samples.